THE ROLE OF PUBLIC HEALTH CENTER IN INDONESIA - Tosepu, Ramadhan; Effendy, Devi Savitri; Ali Imran Ahmad, La Ode; sakka, ambo; Asfian, Pitrah; Lestari, Hariati (Public Health of Indonesia, 2015)
Community health centers have the primary duty as a basic level of health care centers. In performing its duties require professional health workers. Bachelor of public health is one of the health workers who have the ability to move people to live healthy. Strategies to improve health care in community health centers, such as health mapping capabilities, cooperation with other parties, implementing continuous surveillance and conduct health education efforts.